1997
DOI: 10.1177/10454411970080020501
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival Delivery of Therapeutic Agents in the Treatment of Periodontal Diseases

Abstract: This article reviews the current status of controlled local delivery of antibacterial agents in the treatment of periodontitis. The principle of local intrapocket delivery of antibacterial agents and their delivery are discussed. The dosage forms include fibers, film/slabs, and injectable systems, some of which are degradable, while others are not and need to be removed at the termination of the treatment. The antibacterial agents used cover a range of antibiotics as well as antiseptics, and the composition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 55 publications
3
53
0
1
Order By: Relevance
“…Studies with the 25% tetracycline fiber (Goodson, 1994) and a biodegradable chlorhexidine film or chip (Soskolne, 1997) indicated that a seven-to 10-day treatment period is necessary to achieve a clinical result that lasts for several months.…”
Section: (D) Diagnosis Of An Anaerobic Infectionmentioning
confidence: 99%
“…Studies with the 25% tetracycline fiber (Goodson, 1994) and a biodegradable chlorhexidine film or chip (Soskolne, 1997) indicated that a seven-to 10-day treatment period is necessary to achieve a clinical result that lasts for several months.…”
Section: (D) Diagnosis Of An Anaerobic Infectionmentioning
confidence: 99%
“…Compared to systemic drug delivery, local administration in periodontology is considered to be more effective, since the pathogen-specific drug can be placed directly in the periodontal pocket achieving effective concentrations for a sufficiently long period of time. In addition, the risk of undesired side effects caused by high systemic doses or resistance development can be reduced [3,4]. It is therefore beneficial to use local delivery systems that control the release of their agents and guarantee lasting drug concentrations in the pocket in spite of high sulcular fluid rates [3].…”
Section: Introductionmentioning
confidence: 99%
“…A too-quick degradation of the blend fibers to lactic acid could lead to an acidosis and interfere with wound healing. The mechanical stability of the fiber mats is also essential to resist the mechanical stress caused by the high production of sulcus fluid 28) . By the way, the mechanical properties of the composite fiber membranes with naringin are better than that without naringin.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to strengthening by naringin, 6 Dent Mater J 2018; : -which acted as a crystal particle to enhance the polymer composite matrix 24) . Many resorbable drug delivery systems were developed during recent decades, such as drug loaded hydroxypropyl cellulose films 29) , which were first described by Noguchi et al, or drug carrying gels such as Elyzol ® (Dumex, Bad Vilbel, Germany) dental gel, based on melted glycerol mono-oleate 28,[30][31][32] . However, also for these systems, the periodontal milieu often poses the major problem that the required period of drug exposure (7 days) cannot be achieved 28,33) , let alone bone formation which would require several months.…”
Section: Discussionmentioning
confidence: 99%